EXPANDING THE THERAPEUTIC LANDSCAPE OF SMA: SAFETY AND EFFICIENCY OF APITEGROMAB - Urszula Gadomska; Mikołaj Daniluk; Natalia Dejewska; Jowita Wiktoria Maksymiuk; Zuzanna Walewska; Mateusz Onopiuk; Zuzanna Szumska; Szymon Klimaszewski; Jonasz Żuk; Kinga Bukała (International Journal of Innovative Technologies in Social Science, 2026)
Spinal muscular atrophy (SMA) is a genetic disease caused by mutations in the Survival Motor Neuron 1 (SMN1) gene, leading to a deficiency of the SMN protein and progressive degradation of motor neurons and muscle atrophy.Currently, three therapies are available that increase SMN protein levels: nusinersen, risdiplam, and onasemnogene abeparvovec; however, many patients still struggle with persistent motor function deficits. For this reason, an additional form of treatment is needed.The myostatin inhibitor apitegromab is a fully human monoclonal antibody that selectively inhibits the activation of promyostatin and the latent form of myostatin, thereby preventing the release of active myostatin, a negative regulator of muscle growth.The Phase 2 TOPAZ trial demonstrated that apitegromab led to considerable improvements in motor function over 12 months, particularly in younger, nonambulatory patients, where the 20 mg/kg dose resulted in a mean increase in the Hammersmith Functional Motor Scale Expanded (HFMSE) of 7.1 points.Long-term analysis after 36 months from the TOPAZ OLE Study confirmed the durability of these benefits, with nonambulatory patients showing a mean increase of 4.0 points in HFMSE and 2.4 points in RULM. The pivotal phase 3 SAPPHIRE study provided evidence of apitegromab's efficacy. In children aged 2-12 years, a statistically significant improvement of 1.8 points on the HFMSE scale was achieved (p=0.019). In all studies, apitegromab was well tolerated and demonstrated a favorable safety profile. These results show that apitegromab is an effective adjunctive therapy in SMA.